An overview of multi-ingredient kidney stone dissolving formulations from Traditional Persian Pharmacy - Ramin Ansari; Iman Karimzadeh; Majid Nimrouzi; Azadeh Hamedi; Mohammad M. Zarshenas (Shiraz University of Medical Sciences, 2022)
Kidney stone, as a third important urinary tract disease, is a common disease affecting 10-15% of the world population. Effective medical treatment for the disease is not yet well established. On the other hand, there is an increasing global demand to manage and control various diseases with natural medicine and medicaments originating from Complementary and Alternative Medicine (CAM). Traditional Persian medicine (TPM), as one of the most popular schools in CAM, suggests numerous clinical interventions for kidney stones. This review provides various related compound formulations for kidney/bladder stones from the standpoints of Persian scholars. These remedies have been cited in a series of traditional pharmaceutical manuscripts of Persian medicine, namely Qarābādin or prescription. More than fifty multi-ingredient formulations for kidney/bladder stones have been found by reviewing five main Persian pharmacopeias. Various dosage forms have been reported for the management of kidney/bladder stones, such as Majoon (confection), Sharāb (syrup), Jawārish (semisolid confection), Qors (Tablet), and Safoof (oral powder). Considering the positive pharmacological or biological activities of the constituents of filtered formulations, many of those can be re-formulated and either experimentally or clinically evaluated to be introduced as new natural remedies in this field.